2014
DOI: 10.1021/cg500394p
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Single-Step Rapid Synthesis of CuO and Cu2O Nanoparticles from the Same Precursor

Abstract: A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…Figure a and b (3d and e) shows uniform distribution of CuO and TiO 2 nanoparticles of 1CTI (1CTMW) composite. The HRTEM image (Figures c and 3 f) confirms the presence of CuO with (111) plane having lattice fringes of d=0.23 nm and of TiO 2 d=0.35 nm for (101) plane ,,. However, the CuO particle size is significantly high with microwave prepared CT composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a and b (3d and e) shows uniform distribution of CuO and TiO 2 nanoparticles of 1CTI (1CTMW) composite. The HRTEM image (Figures c and 3 f) confirms the presence of CuO with (111) plane having lattice fringes of d=0.23 nm and of TiO 2 d=0.35 nm for (101) plane ,,. However, the CuO particle size is significantly high with microwave prepared CT composite.…”
Section: Resultsmentioning
confidence: 99%
“…There is no specific morphology, except the regular near‐spherical shape for titania particles can be observed. HRTEM analysis of 1CTPD1Pt (Figure c) indicates the presence of Cu 2 O with characteristic inter‐planar spacing for (111) plane; d=0.25 nm corresponds to the cubic structureof Cu 2 O, and for TiO 2 nanoparticles it is found to be 0.35 nm, corresponding to (101) plane of anatase phase ,. From Figure c and 2d, it can be demonstrated that the formation of p‐n junction occurs in the 1CTPD 1Pt composite, which will be helpful for effective separation of charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…All previously reported methods for the synthesis of Cu 2 O particles have required heating of the solution (eg, hydrothermal, polyol, and glucose‐reduction methods). Cu 2 O particles on high‐surface area substrates were prepared by mechanical mixing of solution‐route synthesized Cu 2 O particles and silica gel or the heat treatment of copper‐based precursor supported silica .…”
Section: Discussionmentioning
confidence: 99%
“…[ 68 ] Nikam et al reported the controlled synthesis of Cu 2 O/CuO nanostructures by using an MW‐assisted method, wherein they utilized Cu (II) acetate and Cu (II) acetylacetonate as Cu precursors, and benzyl alcohol as the solvent and reducing agent. [ 69 ] The pH of the solution was varied by introducing small amounts of NaOH, which played an important role in determining the final structure of the products formed. Further, a much more sophisticated technique, that is, encapsulation of CuZn alloy by nitrogen‐doped carbon cages, was introduced by Hu et al to improve the catalytic activity of Cu‐based catalyst.…”
Section: Synthesis Of Cu‐based Catalystsmentioning
confidence: 99%